2017
DOI: 10.15587/1729-4061.2017.112109
|View full text |Cite
|
Sign up to set email alerts
|

Ways to improve operation reliability of traction electric motors of the rolling stock of electric transport

Abstract: Тягові електродвигуни, що використовуються на міському електричному транспорті, забезпечують ефективність роботи електропривода, тому надійність визначає працездатність рухомого складу у цілому. Проаналізовано умови експлуатації тягових електродвигунів, проведено оцінку надійності та визначено шляхи підвищення. Встановлено закономірності зміни параметрів елементів тягових електродвигунів у процесі експлуатації. Розроблено математичну модель оцінки надійності елементів тягових електродвигунівКлючові слова: елек… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 6 publications
0
10
0
8
Order By: Relevance
“…To evaluate the reliability parameters of traction electric motors with small and censored samples on the basis of the utility company "Trolleybus depot No. 3" in Kharkiv, a mathematical model is developed that allows approximating the distribution function for the failure of traction electric motors [12][13][14].…”
Section: Research Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To evaluate the reliability parameters of traction electric motors with small and censored samples on the basis of the utility company "Trolleybus depot No. 3" in Kharkiv, a mathematical model is developed that allows approximating the distribution function for the failure of traction electric motors [12][13][14].…”
Section: Research Resultsmentioning
confidence: 99%
“…As a research result, it is found that the exponential distribution law P 1 (t) of the failure-free operation time of traction electric motors allows to analyze a number of causes of failures during the operation of trolleybuses. This law is also characteristic of trolleybuses, on which errors are made during the operation and repair of traction electric motors [13,14].…”
Section: Engineeringmentioning
confidence: 95%
See 1 more Smart Citation
“…The authors of work [2] note the prospects of using traction motors of direct current at modernizing the traction drive of just the urban electric transport, but the greatest attention is paid to the collector unit.…”
Section: Research Of Existing Solutions Of the Problemmentioning
confidence: 99%
“…Contactless traction drives, based on asynchronous traction motors, remarkable for the high security, are widespread in modern trolleybuses. But the widespread traction drive, based on traction motors of the direct current with combined excitation, is continuously modernized in Ukraine [2].…”
Section: Introductionmentioning
confidence: 99%